A Hospital Based Cross-sectional Study on Demographic Distribution of Both Symptomatic and Asymptomatic Patients an Art at Westren Region of Rajasthan. (Academia Journal of Medicine, 2019)
Background: Over the past two decades with the advent of highly active antiretroviral therapy (HAART), there is a substantial increase in the  life span of HIV patients. Morbidity and mortality due to human immunodeficiency virus (HIV) continue to be major problems in developing  countries like India. Subjects and Methods: The present study was a cross sectional hospital based study for a period of twelve months from  1st Nov. 2015 to 31st Oct. 2016 at ART center P.B.M. Hospital, Bikaner. 100 HIV+ patients on ART were included in the study by  consecutive sampling technique. Results: We found that Maximum number of study participants in age group of 31-40 years in both study  (50%) and control (42%) group. Males were higher in study (76%) as well as control (64%) group than females .Among the subjects mostly belonged to lower socioeconomic status followed by Medium and High socioeconomic status. Most of the subjects in study (92%) as well as  control (94%) groups were married. Conclusion: We conclude that Males were higher in study (76%) as well as control (64%) group than  females .Among the subjects mostly belonged to lower socioeconomic status followed by Medium and High socioeconomic status.
Keywords: Haart; Haart Hiv; Morbidity; Mortality